A titanium alloy surface treatment process

Through specific sequential surface treatment processes and surface modifications, the problems of weak interface effects and poor adhesive performance in surface treatment of titanium alloys are solved, and the adhesive performance and durability of titanium alloys and resin materials are significantly improved.

CN118600504BActive Publication Date: 2024-12-17DONGGUAN YUKUN NANO INJECTION TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410810504.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-21
Publication Date
2024-12-17
Estimated Expiration
2044-06-21

AI Technical Summary

Technical Problem

The existing titanium alloy surface treatment technology leads to weak interface between resin material and titanium alloy and poor bonding performance. There is uneven adhesion of cavity and surface when the micropores on the surface of titanium alloy are combined with the viscous resin, resulting in bonding durability Low.

Method used

Using a specific sequence of surface treatment processes, including degreasing, pickling, alkaline anodization, shot peening, acid anodization, and surface modification in dopamine solution and eugenol glycidyl ether solution to form a composite film to enhance Mechanical linkage and chemical bonding points.

Benefits of technology

The bonding area and interface bonding force between the surface of the titanium alloy and the resin material is significantly improved, the bonding performance and durability are enhanced, the surface energy of the oxide film is improved, and the resistance to environmental factors is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004906030350000101
    Figure BDA0004906030350000101
Patent Text Reader

Abstract

The present invention relates to the technical field of titanium alloy surface treatment, specifically to a titanium alloy surface treatment process. Step 1: Degreasing and pickling the titanium alloy in sequence to obtain titanium alloy A; Step 2: Alkaline anodizing, shot peening and acid anodizing the titanium alloy A in sequence to obtain titanium alloy B; Step 3: Dipping titanium alloy B in a dopamine solution; transferring to a eugenol glycidyl ether solution for surface modification; washing and drying to obtain a titanium alloy finished product. In the scheme, the surface roughening treatment and the coordinated organic surface modification treatment can effectively improve the interface effect when the titanium alloy surface is bonded with the polymer, and increase the bonding strength and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium alloy surface treatment, in particular to a titanium alloy surface treatment process. Background Art

[0002] Titanium alloy is a metal structural material with high strength, high temperature resistance and good corrosion resistance. It is widely used in various industrial fields such as aerospace, medical, electronic equipment, optics, etc. However, in the industrial field, it is usually necessary to combine titanium alloy with resin materials to enhance its applicability. Therefore, it is necessary to perform surface treatment such as roughening on the titanium alloy surface to produce micropores on the surface and improve the bonding between the metal surface and the resin material.

[0003] The surface treatment of titanium alloy usually includes plasma treatment, sandblasting, acid etching, anodizing, etc., but the prior art still has the following defects: First, the interface effect between the resin material and the surface treated titanium alloy is still weak, and the bonding performance is poor; second, when the micropores on the surface of the titanium alloy are compounded with the relatively viscous resin, there are cavities and surface adhesion unevenness, resulting in poor bonding performance and low bonding durability.

[0004] In summary, it is of great significance to improve the defects of the existing technology and form a new titanium alloy surface treatment process. Summary of the invention

[0005] The purpose of the present invention is to provide a titanium alloy surface treatment process to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a titanium alloy surface treatment process, comprising the following steps:

[0007] Step 1: Degreasing and pickling the titanium alloy in sequence to obtain titanium alloy A;

[0008] Step 2: titanium alloy A is subjected to alkaline anodizing, shot peening, and acid anodizing in sequence to obtain titanium alloy B;

[0009] Step 3: Place titanium alloy B in a dopamine solution for immersion treatment; transfer it to a eugenol glycidyl ether solution for surface modification; wash and dry to obtain a titanium alloy product.

[0010] In a further scheme, step 1 specifically includes the following process: the titanium alloy is first placed in an alkaline solution and degreased at 50-55°C for 30-50 minutes; then transferred to an acidic solution, pickled at room temperature for 15-30 minutes, washed with deionized water, and dried with nitrogen to obtain titanium alloy A.

[0011] In a further embodiment, the alkaline solution comprises the following components: 30-40 g / L sodium tripolyphosphate, 10-15 g / L sodium tetraborate, 0.5-1 g / L 3-methacryloyl dopamine, and the solvent is deionized water.

[0012] In a further embodiment, the alkaline solution comprises the following components: the acidic solution comprises the following components: 30-50 mL / L of hydrofluoric acid, 30-50 mL / L of nitric acid, 0.2-0.5 g / L of methacrylic acid sulfobetaine, and the solvent is deionized water.

[0013] In a further solution, step 2 specifically includes the following process:

[0014] S21: placing titanium alloy A in an alkaline anodizing solution, setting a voltage of 5 to 15 V, anodizing at room temperature for 10 to 20 minutes, washing with deionized water, and drying with nitrogen to obtain titanium alloy A1;

[0015] S22: Shot peening the titanium alloy A1 for 2 to 10 minutes, setting the parameters as follows: shot peening with steel shot having a diameter of 5 to 6 mm, a vibration frequency of 5 to 7 Hz, an amplitude of 50 to 60 mm, washing with deionized water, and drying with nitrogen to obtain titanium alloy A2;

[0016] S23: Place titanium alloy A2 in an acidic anodizing solution, set the voltage to 30-50 V, anodize for 15-20 minutes at room temperature, wash with deionized water, blow dry with nitrogen, and titanium alloy B.

[0017] In a further embodiment, the alkaline anodizing solution comprises the following components: 20-40wt% sodium hydroxide, 1-2wt% ethylenediaminetetraacetic acid, 4-6wt% sodium tartrate, 0.3-0.5wt% sodium silicate, 0.3-0.5wt% ammonium fluoride, and the solvent is 15-20wt% ethylene glycol aqueous solution.

[0018] In a further embodiment, the acidic anodizing solution comprises the following components: 4-6 wt% phosphoric acid, 1-1.5 wt% tannic acid, and 0.2-0.5 wt% methacrylate sulfobetaine.

[0019] In a further solution, step 3 specifically includes the following process:

[0020] The titanium alloy B is placed in a dopamine solution, subjected to ultrasound at a frequency of 25 to 38 kHz for 10 to 20 minutes, and oscillated at 60 to 80 rpm for 2 to 6 hours; transferred to a eugenol glycidyl ether solution, and oscillated at 60 to 80 rpm for 2 to 3 hours under ultraviolet light; washed, and dried at 60 to 70° C. to obtain a titanium alloy product.

[0021] In a further embodiment, the dopamine solution comprises the following components: 0.8-1 mg / mL dopamine, 0.7-0.9 mg / mL 3-methacryloyl dopamine, 0.5-0.6 mg / mL amino-modified methacrylic acid sulfobetaine, and the solvent is 0.1 M Tris-buffered solution.

[0022] The preparation method of amino-modified methacrylate sulfobetaine is as follows: methacrylate sulfobetaine and cysteamine are added to deionized water in a molar ratio of 1:1, a photoinitiator (photoinitiator AIBN) is added, and the mixture is stirred for reaction for 1 to 2 hours under ultraviolet light, and post-treated to obtain amino-modified methacrylate sulfobetaine.

[0023] In a further embodiment, the eugenol glycidyl ether solution comprises the following components: 7-8 wt % of eugenol glycidyl ether, 2-3 wt % of 2,3-dimercapto-1-propanol, 0.01-0.02 wt % of a photoinitiator, and the solvent is acetone.

[0024] Among them, the preparation method of eugenol glycidyl ether is: epichlorohydrin and eugenol are mixed in a molar ratio of 3:1, a catalyst (benzyltriethylammonium chloride, accounting for 1wt% of the total mass of epichlorohydrin and eugenol) is added, and the mixture is reacted at 95-100°C for 4-6 hours under a nitrogen atmosphere, cooled to 55-60°C, a 30wt% sodium hydroxide solution is added dropwise, the reaction is continued for 4-6 hours, and post-processed to obtain eugenol glycidyl ether.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) In the scheme, the titanium alloy is degreased and pickled in sequence to form a titanium alloy A with a roughened surface; then the surface is subjected to a specific sequence of surface micropore treatments, including alkaline anodizing, shot peening, and acid anodizing in sequence, so as to construct a titanium alloy surface with micro / nano roughness on the surface, thereby promoting mechanical interlocking, increasing the bonding area between the surface and the resin material, and improving the bonding performance. In the prior art, single anodizing is usually used. In the scheme, alkaline anodizing is first used to form a pore structure to provide a mechanical anchor point, and subsequent shot peening and acid anodizing further expand the pores to improve the surface energy of the oxide film, thereby enhancing the anchor point, increasing the chemical bonding points between the resin material and the resin material, thereby improving the interface bonding force and bonding strength. In addition, due to the two-step anodizing process, the composite film formed has better durability and can better resist the erosion of environmental factors, thereby improving performance.

[0027] In addition, unlike the existing shot peening treatment in the early stage, the solution introduces shot peening in the two-step anodizing process. First, it can remove loose particles and contaminants generated in the alkaline anodizing process, release stress in the alkaline anodizing process, optimize the pore structure, and provide a better surface for the next step of acid anodizing. Shot peening can also increase the surface roughness, thereby providing more mechanical anchoring and improving the bonding performance. The steps of alkaline anodizing and acid anodizing cannot be changed, otherwise it will cause cracks in the surface oxide film and affect the surface performance.

[0028] (2) In order to solve the problem of poor permeability of adhesive resin and the presence of interfacial pores with the titanium metal surface affecting the durability of adhesive bonding, dopamine solution and eugenol glycidyl ether solution were further used for surface modification. The molecular weight of the substances in the two solutions was small, and the ultrasound and oscillation processes were conducive to the entry of molecules. At the same time, ultraviolet light was used to cross-link the infiltrated substances, similar to sealing the pores, reducing the porosity. At the same time, reactive and compatible groups were further introduced for mechanical anchoring, thereby effectively improving the bonding performance with the resin material. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] It should be noted that the purchase manufacturers of all raw materials involved in the present invention are exemplified without any special restrictions: in the following embodiments, the CAS number of methacrylic acid sulfobetaine is 3637-26-1, the CAS number of dopamine is 51-61-6, the CAS number of 3-methacryloyl dopamine is 471915-89-64, and the CAS number of 2,3-dimercapto-1-propanol is 59-52-9; all are commercially available.

[0031] Pre-preparation: (1) Preparation of amino-modified methacrylic acid sulfobetaine: add methacrylic acid sulfobetaine and cysteamine in a molar ratio of 1:1 to deionized water, add photoinitiator AIBN (accounting for 0.5wt% of the total mass of methacrylic acid sulfobetaine and cysteamine), stir and react for 2 hours under ultraviolet light, and post-treat to obtain amino-modified methacrylic acid sulfobetaine. (2) Preparation of eugenol glycidyl ether: mix epichlorohydrin and eugenol in a molar ratio of 3:1, add benzyltriethylammonium chloride catalyst (accounting for 1wt% of the total mass of epichlorohydrin and eugenol), react at 100°C for 5 hours under nitrogen atmosphere, cool to 60°C, add 30wt% sodium hydroxide solution (sodium hydroxide accounts for 25wt% of epichlorohydrin), continue to react for 5 hours, and post-treat to obtain eugenol glycidyl ether.

[0032] Embodiment 1: A titanium alloy surface treatment process comprises the following steps:

[0033] Step 1: The titanium alloy is first placed in an alkaline solution and degreased at 55°C for 50 minutes; then transferred to an acidic solution, pickled at room temperature for 15 minutes, washed with deionized water, and dried with nitrogen to obtain titanium alloy A;

[0034] The alkaline solution includes the following components: 35 g / L sodium tripolyphosphate, 15 g / L sodium tetraborate, 1 g / L 3-methacryloyl dopamine, and the solvent is deionized water; the acidic solution includes the following components: 50 mL / L hydrofluoric acid, 30 mL / L nitric acid, 0.5 g / L methacrylic acid sulfobetaine, and the solvent is deionized water;

[0035] Step 2: S21: placing titanium alloy A in an alkaline anodizing solution, setting the voltage to 15 V, anodizing at room temperature for 15 minutes, washing with deionized water, and drying with nitrogen to obtain titanium alloy A1; the alkaline anodizing solution comprises the following components: 30wt% sodium hydroxide, 2wt% ethylenediaminetetraacetic acid, 5wt% sodium tartrate, 0.5wt% sodium silicate, 0.5wt% ammonium fluoride, and the solvent is 20wt% ethylene glycol aqueous solution;

[0036] S22: Shot peening the titanium alloy A1 for 5 minutes, setting the parameters as follows: shot peening with steel shot having a diameter of 6 mm, a vibration frequency of 7 Hz, an amplitude of 60 mm, washing with deionized water, and drying with nitrogen to obtain titanium alloy A2;

[0037] S23: titanium alloy A2 is placed in an acidic anodizing solution, the voltage is set to 50 V, anodized at room temperature for 15 minutes, washed with deionized water, and dried with nitrogen gas, titanium alloy B; the acidic anodizing solution includes the following components: 5wt% phosphoric acid, 1wt% tannic acid, and 0.5wt% methacrylic acid sulfobetaine;

[0038] Step 3: Place titanium alloy B in a dopamine solution, perform ultrasound at a frequency of 38KHz for 15 minutes, and oscillate at 60rpm for 4 hours; transfer to a eugenol glycidyl ether solution, oscillate at 60rpm for 2 hours under ultraviolet light; wash, and dry at 70°C to obtain a titanium alloy product;

[0039] The dopamine solution comprises the following components: 0.9 mg / mL dopamine, 0.9 mg / mL 3-methacryloyl dopamine, 0.6 mg / mL amino-modified methacrylic acid sulfobetaine, and the solvent is 0.1 M Tris-buffer solution; the eugenol glycidyl ether solution comprises the following components: 8 wt % eugenol glycidyl ether, 2 wt % 2,3-dimercapto-1-propanol, 0.01 wt % photoinitiator 651, and the solvent is acetone.

[0040] Embodiment 2: A titanium alloy surface treatment process, comprising the following steps:

[0041] Step 1: The titanium alloy is first placed in an alkaline solution and degreased at 55°C for 50 minutes; then transferred to an acidic solution, pickled at room temperature for 15 minutes, washed with deionized water, and dried with nitrogen to obtain titanium alloy A;

[0042] The alkaline solution includes the following components: 35 g / L sodium tripolyphosphate, 15 g / L sodium tetraborate, 1 g / L 3-methacryloyl dopamine, and the solvent is deionized water; the acidic solution includes the following components: 50 mL / L hydrofluoric acid, 30 mL / L nitric acid, 0.5 g / L methacrylic acid sulfobetaine, and the solvent is deionized water;

[0043] Step 2: S21: placing titanium alloy A in an alkaline anodizing solution, setting the voltage to 5V, anodizing at room temperature for 20 minutes, washing with deionized water, and drying with nitrogen to obtain titanium alloy A1; the alkaline anodizing solution comprises the following components: 40wt% sodium hydroxide, 1wt% ethylenediaminetetraacetic acid, 4wt% sodium tartrate, 0.3wt% sodium silicate, 0.3wt% ammonium fluoride, and the solvent is 20wt% ethylene glycol aqueous solution;

[0044] S22: Shot peening the titanium alloy A1 for 5 minutes, setting the parameters as follows: shot peening with steel shot having a diameter of 6 mm, a vibration frequency of 7 Hz, an amplitude of 60 mm, washing with deionized water, and drying with nitrogen to obtain titanium alloy A2;

[0045] S23: titanium alloy A2 is placed in an acidic anodizing solution, the voltage is set to 50 V, anodized at room temperature for 15 minutes, washed with deionized water, and dried with nitrogen gas, titanium alloy B; the acidic anodizing solution includes the following components: 4wt% phosphoric acid, 1wt% tannic acid, and 0.2wt% methacrylic acid sulfobetaine;

[0046] Step 3: Place titanium alloy B in a dopamine solution, perform ultrasound at a frequency of 38KHz for 15 minutes, and oscillate at 60rpm for 4 hours; transfer to a eugenol glycidyl ether solution, oscillate at 60rpm for 2 hours under ultraviolet light; wash, and dry at 70°C to obtain a titanium alloy product;

[0047] The dopamine solution comprises the following components: 0.8 mg / mL dopamine, 0.9 mg / mL 3-methacryloyl dopamine, 0.5 mg / mL amino-modified methacrylic acid sulfobetaine, and the solvent is 0.1 M Tris-buffer solution; the eugenol glycidyl ether solution comprises the following components: 8 wt % eugenol glycidyl ether, 2 wt % 2,3-dimercapto-1-propanol, 0.01 wt % photoinitiator 651, and the solvent is acetone.

[0048] Embodiment 3: A titanium alloy surface treatment process, comprising the following steps:

[0049] Step 1: The titanium alloy is first placed in an alkaline solution and degreased at 55°C for 50 minutes; then transferred to an acidic solution, pickled at room temperature for 15 minutes, washed with deionized water, and dried with nitrogen to obtain titanium alloy A;

[0050] The alkaline solution includes the following components: 35 g / L sodium tripolyphosphate, 15 g / L sodium tetraborate, 1 g / L 3-methacryloyl dopamine, and the solvent is deionized water; the acidic solution includes the following components: 50 mL / L hydrofluoric acid, 30 mL / L nitric acid, 0.5 g / L methacrylic acid sulfobetaine, and the solvent is deionized water;

[0051] Step 2: S21: placing titanium alloy A in an alkaline anodizing solution, setting the voltage to 15 V, anodizing at room temperature for 10 minutes, washing with deionized water, and drying with nitrogen to obtain titanium alloy A1; the alkaline anodizing solution comprises the following components: 20wt% sodium hydroxide, 2wt% ethylenediaminetetraacetic acid, 6wt% sodium tartrate, 0.5wt% sodium silicate, 0.5wt% ammonium fluoride, and the solvent is 15wt% ethylene glycol aqueous solution;

[0052] S22: Shot peening the titanium alloy A1 for 5 minutes, setting the parameters as follows: shot peening with steel shot having a diameter of 6 mm, a vibration frequency of 7 Hz, an amplitude of 60 mm, washing with deionized water, and drying with nitrogen to obtain titanium alloy A2;

[0053] S23: titanium alloy A2 is placed in an acidic anodizing solution, the voltage is set to 50 V, anodized at room temperature for 15 minutes, washed with deionized water, and dried with nitrogen gas, titanium alloy B; the acidic anodizing solution includes the following components: 6wt% phosphoric acid, 1.5wt% tannic acid, and 0.5wt% methacrylate sulfobetaine;

[0054] Step 3: Place titanium alloy B in a dopamine solution, perform ultrasound at a frequency of 38KHz for 15 minutes, and oscillate at 60rpm for 4 hours; transfer to a eugenol glycidyl ether solution, oscillate at 60rpm for 2 hours under ultraviolet light; wash, and dry at 70°C to obtain a titanium alloy product;

[0055] The dopamine solution comprises the following components: 1 mg / mL dopamine, 0.7 mg / mL 3-methacryloyl dopamine, 0.5 mg / mL amino-modified methacrylic acid sulfobetaine, and the solvent is 0.1 M Tris-buffer solution; the eugenol glycidyl ether solution comprises the following components: 7 wt % eugenol glycidyl ether, 3 wt % 2,3-dimercapto-1-propanol, 0.02 photoinitiator 651, and the solvent is acetone.

[0056] Comparative Example 1: Referring to Example 1, single alkaline anodizing; a titanium alloy surface treatment process, comprising the following steps:

[0057] Step 1: The titanium alloy is first placed in an alkaline solution and degreased at 55°C for 50 minutes; then transferred to an acidic solution, pickled at room temperature for 15 minutes, washed with deionized water, and dried with nitrogen to obtain titanium alloy A;

[0058] The alkaline solution includes the following components: 35 g / L sodium tripolyphosphate, 15 g / L sodium tetraborate, 1 g / L 3-methacryloyl dopamine, and the solvent is deionized water; the acidic solution includes the following components: 50 mL / L hydrofluoric acid, 30 mL / L nitric acid, 0.5 g / L methacrylic acid sulfobetaine, and the solvent is deionized water;

[0059] Step 2: placing titanium alloy A in an alkaline anodizing solution, setting the voltage to 15 V, anodizing at room temperature for 15 minutes, washing with deionized water, and drying with nitrogen to obtain titanium alloy A1; the alkaline anodizing solution comprises the following components: 30wt% sodium hydroxide, 2wt% ethylenediaminetetraacetic acid, 5wt% sodium tartrate, 0.5wt% sodium silicate, 0.5wt% ammonium fluoride, and the solvent is 20wt% ethylene glycol aqueous solution;

[0060] Step 3: Place titanium alloy A1 in a dopamine solution, perform ultrasound at a frequency of 38KHz for 15 minutes, and oscillate at 60rpm for 4 hours; transfer to a eugenol glycidyl ether solution, oscillate at 60rpm for 2 hours under ultraviolet light; wash, and dry at 70°C to obtain a titanium alloy product;

[0061] The dopamine solution comprises the following components: 0.9 mg / mL dopamine, 0.9 mg / mL 3-methacryloyl dopamine, 0.6 mg / mL amino-modified methacrylic acid sulfobetaine, and the solvent is 0.1 M Tris-buffer solution; the eugenol glycidyl ether solution comprises the following components: 8 wt % eugenol glycidyl ether, 2 wt % 2,3-dimercapto-1-propanol, 0.01 wt % photoinitiator 651, and the solvent is acetone.

[0062] Comparative Example 2: Referring to Example 1, acid anodization is first performed and then alkaline anodization is performed; a titanium alloy surface treatment process comprises the following steps:

[0063] Step 1: The titanium alloy is first placed in an alkaline solution and degreased at 55°C for 50 minutes; then transferred to an acidic solution, pickled at room temperature for 15 minutes, washed with deionized water, and dried with nitrogen to obtain titanium alloy A;

[0064] The alkaline solution includes the following components: 35 g / L sodium tripolyphosphate, 15 g / L sodium tetraborate, 1 g / L 3-methacryloyl dopamine, and the solvent is deionized water; the acidic solution includes the following components: 50 mL / L hydrofluoric acid, 30 mL / L nitric acid, 0.5 g / L methacrylic acid sulfobetaine, and the solvent is deionized water;

[0065] Step 2: S21: placing titanium alloy A in an acidic anodizing solution, setting the voltage to 50 V, anodizing at room temperature for 15 minutes, washing with deionized water, and drying with nitrogen, titanium alloy A1; the acidic anodizing solution comprises the following components: 5wt% phosphoric acid, 1wt% tannic acid, and 0.5wt% methacrylic acid sulfobetaine;

[0066] S22: Shot peening the titanium alloy A1 for 5 minutes, setting the parameters as follows: shot peening with steel shot having a diameter of 6 mm, a vibration frequency of 7 Hz, an amplitude of 60 mm, washing with deionized water, and drying with nitrogen to obtain titanium alloy A2;

[0067] S23: placing titanium alloy A2 in an alkaline anodizing solution, setting the voltage to 15 V, anodizing at room temperature for 15 minutes, washing with deionized water, and drying with nitrogen to obtain titanium alloy B; the alkaline anodizing solution comprises the following components: 30 wt % sodium hydroxide, 2 wt % ethylenediaminetetraacetic acid, 5 wt % sodium tartrate, 0.5 wt % sodium silicate, 0.5 wt % ammonium fluoride, and the solvent is 20 wt % ethylene glycol aqueous solution;

[0068] Step 3: Place titanium alloy B in a dopamine solution, perform ultrasound at a frequency of 38KHz for 15 minutes, and oscillate at 60rpm for 4 hours; transfer to a eugenol glycidyl ether solution, oscillate at 60rpm for 2 hours under ultraviolet light; wash, and dry at 70°C to obtain a titanium alloy product;

[0069] The dopamine solution comprises the following components: 0.9 mg / mL dopamine, 0.9 mg / mL 3-methacryloyl dopamine, 0.6 mg / mL amino-modified methacrylic acid sulfobetaine, and the solvent is 0.1 M Tris-buffer solution; the eugenol glycidyl ether solution comprises the following components: 8 wt % eugenol glycidyl ether, 2 wt % 2,3-dimercapto-1-propanol, 0.01 wt % photoinitiator 651, and the solvent is acetone.

[0070] Comparative Example 3: Referring to Example 1, shot peening is not performed; a titanium alloy surface treatment process comprises the following steps:

[0071] Step 1: The titanium alloy is first placed in an alkaline solution and degreased at 55°C for 50 minutes; then transferred to an acidic solution, pickled at room temperature for 15 minutes, washed with deionized water, and dried with nitrogen to obtain titanium alloy A;

[0072] The alkaline solution includes the following components: 35 g / L sodium tripolyphosphate, 15 g / L sodium tetraborate, 1 g / L 3-methacryloyl dopamine, and the solvent is deionized water; the acidic solution includes the following components: 50 mL / L hydrofluoric acid, 30 mL / L nitric acid, 0.5 g / L methacrylic acid sulfobetaine, and the solvent is deionized water;

[0073] Step 2: S21: placing titanium alloy A in an alkaline anodizing solution, setting the voltage to 15 V, anodizing at room temperature for 15 minutes, washing with deionized water, and drying with nitrogen to obtain titanium alloy A1; the alkaline anodizing solution comprises the following components: 30wt% sodium hydroxide, 2wt% ethylenediaminetetraacetic acid, 5wt% sodium tartrate, 0.5wt% sodium silicate, 0.5wt% ammonium fluoride, and the solvent is 20wt% ethylene glycol aqueous solution;

[0074] S22: titanium alloy A1 is placed in an acidic anodizing solution, the voltage is set to 50 V, anodized at room temperature for 15 minutes, washed with deionized water, and dried with nitrogen gas, titanium alloy B; the acidic anodizing solution includes the following components: 5wt% phosphoric acid, 1wt% tannic acid, and 0.5wt% methacrylic acid sulfobetaine;

[0075] Step 3: Place titanium alloy B in a dopamine solution, perform ultrasound at a frequency of 38KHz for 15 minutes, and oscillate at 60rpm for 4 hours; transfer to a eugenol glycidyl ether solution, oscillate at 60rpm for 2 hours under ultraviolet light; wash, and dry at 70°C to obtain a titanium alloy product;

[0076] The dopamine solution comprises the following components: 0.9 mg / mL dopamine, 0.9 mg / mL 3-methacryloyl dopamine, 0.6 mg / mL amino-modified methacrylic acid sulfobetaine, and the solvent is 0.1 M Tris-buffer solution; the eugenol glycidyl ether solution comprises the following components: 8 wt % eugenol glycidyl ether, 2 wt % 2,3-dimercapto-1-propanol, 0.01 wt % photoinitiator 651, and the solvent is acetone.

[0077] Comparative Example 4: Referring to Example 1, only a single dopamine solution treatment is performed, and no eugenol glycidyl ether solution modification is performed; a titanium alloy surface treatment process comprises the following steps:

[0078] Step 1: The titanium alloy is first placed in an alkaline solution and degreased at 55°C for 50 minutes; then transferred to an acidic solution, pickled at room temperature for 15 minutes, washed with deionized water, and dried with nitrogen to obtain titanium alloy A;

[0079] The alkaline solution includes the following components: 35 g / L sodium tripolyphosphate, 15 g / L sodium tetraborate, 1 g / L 3-methacryloyl dopamine, and the solvent is deionized water; the acidic solution includes the following components: 50 mL / L hydrofluoric acid, 30 mL / L nitric acid, 0.5 g / L methacrylic acid sulfobetaine, and the solvent is deionized water;

[0080] Step 2: S21: placing titanium alloy A in an alkaline anodizing solution, setting the voltage to 15 V, anodizing at room temperature for 15 minutes, washing with deionized water, and drying with nitrogen to obtain titanium alloy A1; the alkaline anodizing solution comprises the following components: 30wt% sodium hydroxide, 2wt% ethylenediaminetetraacetic acid, 5wt% sodium tartrate, 0.5wt% sodium silicate, 0.5wt% ammonium fluoride, and the solvent is 20wt% ethylene glycol aqueous solution;

[0081] S22: Shot peening the titanium alloy A1 for 5 minutes, setting the parameters as follows: shot peening with steel shot having a diameter of 6 mm, a vibration frequency of 7 Hz, an amplitude of 60 mm, washing with deionized water, and drying with nitrogen to obtain titanium alloy A2;

[0082] S23: titanium alloy A2 is placed in an acidic anodizing solution, the voltage is set to 50 V, anodized at room temperature for 15 minutes, washed with deionized water, and dried with nitrogen gas, titanium alloy B; the acidic anodizing solution includes the following components: 5wt% phosphoric acid, 1wt% tannic acid, and 0.5wt% methacrylic acid sulfobetaine;

[0083] Step 3: placing titanium alloy B in a dopamine solution, ultrasonicating at a frequency of 38KHz for 15 minutes, and oscillating at 60rpm for 4 hours; washing, and drying at 70°C to obtain a titanium alloy product;

[0084] The dopamine solution comprises the following components: 0.9 mg / mL dopamine, 0.9 mg / mL 3-methacryloyl dopamine, 0.6 mg / mL amino-modified methacrylic acid sulfobetaine, and the solvent is 0.1 M Tris-buffer solution.

[0085] Performance test: The titanium alloy products prepared in the examples and comparative examples were bonded to the carbon fiber CCF300 / epoxy resin 5228 composite material, the adhesive was J-27-2 epoxy resin adhesive, and the curing condition was 180°C for 1.5 hours; the bonding strength A was tested, and after aging for 1000 hours at 55°C and 95% humidity, the bonding strength B was tested again. The obtained data are shown in the following table:

[0086]

[0087] Conclusion: It can be seen from the data in the above table that the surface treatment process of the titanium alloy in the present application effectively improves its bonding performance and bonding durability with the resin material; from the data of comparative examples 1 to 4, it can be seen that the two-step anodizing in a specific order in the scheme, and the shot peening treatment between the two-step anodizing further improve the bonding performance; in addition, further modification with eugenol glycidyl ether solution can effectively improve the interface effect, thereby improving the bonding performance.

[0088] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A titanium alloy surface treatment process, Features: The following steps are involved: Step 1: Degreasing and pickling the titanium alloy in sequence to obtain titanium alloy A; Step 2: S21: placing titanium alloy A in an alkaline anodizing solution, setting the voltage to 5 to 15 V, anodizing at room temperature for 10 to 20 minutes, washing with deionized water, and drying with nitrogen to obtain titanium alloy A1; S22: Shot peening the titanium alloy A1 for 2 to 10 minutes, setting the parameters as follows: shot peening with steel shot having a diameter of 5 to 6 mm, a vibration frequency of 5 to 7 Hz, an amplitude of 50 to 60 mm, washing with deionized water, and drying with nitrogen to obtain titanium alloy A2; S23: placing titanium alloy A2 in an acidic anodizing solution, setting the voltage to 30-50 V, anodizing for 15-20 minutes at room temperature, washing with deionized water, drying with nitrogen, titanium alloy B; Step 3: Place titanium alloy B in a dopamine solution, perform ultrasound at a frequency of 25 to 38 kHz for 10 to 20 minutes, and oscillate at 60 to 80 rpm for 2 to 6 hours; transfer to a eugenol glycidyl ether solution, and oscillate at 60 to 80 rpm for 2 to 3 hours under ultraviolet light; Washing, drying at 60-70°C to obtain a titanium alloy product; The alkaline anodizing solution comprises the following components: 20-40 wt% sodium hydroxide, 1-2 wt% ethylenediaminetetraacetic acid, 4-6 wt% sodium tartrate, 0.3-0.5 wt% sodium silicate, 0.3-0.5 wt% ammonium fluoride, and the solvent is 15-20 wt% ethylene glycol aqueous solution; The acidic anodizing solution comprises the following components: 4-6 wt% phosphoric acid, 1-1.5 wt% tannic acid, and 0.2-0.5 wt% methacrylate sulfobetaine.

2. A titanium alloy surface treatment process according to claim 1, Features: Step 1 The method comprises the following steps: firstly placing the titanium alloy in an alkaline solution, and performing a degreasing treatment at 50-55° C. for 30-50 minutes; then transferring the titanium alloy to an acidic solution, performing an acid pickling treatment at room temperature for 15-30 minutes, washing with deionized water, and drying with nitrogen to obtain titanium alloy A.

3. A titanium alloy surface treatment process according to claim 2, Features: The alkaline solution comprises the following components: 30-40 g / L of sodium tripolyphosphate, 10-15 g / L of sodium tetraborate, 0.5-1 g / L of 3-methacryloyl dopamine, and the solvent is deionized water.

4. A titanium alloy surface treatment process according to claim 2, Features: The acidic solution comprises the following components: 30-50 mL / L of hydrofluoric acid, 30-50 mL / L of nitric acid, 0.2-0.5 g / L of methacrylic acid sulfobetaine, and the solvent is deionized water.

5. A titanium alloy surface treatment process according to claim 1, Features: The dopamine solution comprises the following components: 0.8-1 mg / mL dopamine, 0.7-0.9 mg / mL 3-methacryloyl dopamine, 0.5-0.6 mg / mL amino-modified methacrylic acid sulfobetaine, and the solvent is 0.1 M Tris-buffer solution.

6. A titanium alloy surface treatment process according to claim 1, Features: The eugenol glycidyl ether solution comprises the following components: 7-8 wt % of eugenol glycidyl ether, 2-3 wt % of 2,3-dimercapto-1-propanol, 0.01-0.02 wt % of a photoinitiator, and the solvent is acetone.

Citation Information

Patent Citations

  • Method for creating an anti-infection coating on an implant

    CN102271721A

  • Pellicle frame and process for producing same

    US20160259239A1

  • Resin-titanium metal bonded body and method for manufacturing same

    WO2019050040A1